FRI0679 Whole spine and SIJ MRI of psoriatic arthritis patients: descriptive study of the spine, and sacroiliac joints involvement in a cross sectional large cohort. (15th June 2017) - Furer, V; Stark, M; Matz, H; Levartovsky, D; Wollman, J; Wigler, I; Sarbagil-Maman, H; Paran, D; Kaufman, I; Anouk, M; Borok, S; Zemah, R; et al.
Abstract : Background: Detection of axial disease has important implications. Data on the structural changes of the spine and SIJ in PsA is mainly based on plain XR and MRI of SIJ. The prevalence and distribution of spinal changes in PsA as detected by MRI is largely unknown. Objectives: To evaluate acute and structural changes in spine and SIJ by whole spine MRI performed in a consecutive clinical cohort of PsA. Methods: Adult PsA (CASPAR criteria) patients were enrolled in the study. All underwent clinical exam, CRP, HLA-B27 tests, and MRI of the entire spine and SIJ. Spinal sagittal T1-W, STIR and semi-coronal T1-W and T2-W with fat saturation sequences of the SIJ were performed. The spine was scored for the presence of syndesmophytes, bone marrow edema (BME)/fatty corners and enthesitis. SIJS were scored (Berlin score) for the presence of BME, fatty replacement, erosions, sclerosis, and ankylosis. Findings were further categorized into active sacroiliitis (ASAS 1 ), structural sacroiliitis, and spinal findings compatible with SpA (≥3 BME or ≥4 fatty corners 2 ). All MRIs were evaluated by an experienced musculoskeletal radiologist, blinded to clinical data. Data were analyzed by SPSS Version 20.0. Results: Ninety six patients completed the study.(Table1 ) Active/structural/total sacroiliitis was detected in 26%/11.5%/37.5% of patients, respectively. Spinal SpA was demonstrated in 15.6%.(Table 2) Isolated spinal changes were detected in 2.1% of the cohort. Presence of inflammatory back pain (IBP) by ASAS correlated with the prevalence of active sacroiliitis (p 0.024) and SpA (axial/SIJ) (p 0.003). The extent of psoriasis severity (PASI) correlated with both SIJ and whole spine SpA changes. ( p 0.02 for both ) Gender differences or biologic therapy did not affect the prevalence of SIJ or spine involvement. Conclusions: In the present PsA cohort, active and structural sacroiliitis was more prevalent vs typical spinal SpA changes. In particular, there was a paucity of SpA changes in the cervical spine. The most prominent axial findings included fatty corners and syndesmophytes. IBP presence and extensive skin disease correlated with SpA axial and SIJ changes. References: Lambert RG. Ann Rheum Dis. 2016, 75. Hermann KG. Ann Rheum Dis 2012.71. Disclosure of Interest: None declared